EFL Students’ Perceptions about their English Language Learning and its Uses for Specific Purposes at International Languages Institute at Uptc Duitama Branch - Puerto Zabala, Paola Yesenia; Reyes Vargas, Rosalba (Universidad Pedagógica y Tecnológica de Colombia, 2014)
AbstractThis article reports a small scale study that revealed the perceptions students have inTechnology and Industrial Administration major programs. The main objective of thisstudy was to reveal the perceptions of these students about their English learning and itsuse for specific purposes. This study was carried out with students who are takingEnglish as a foreign language at the Languages Institute at Universidad Pedagógica y Tecnológica de Colombia, Duitama branch. The paper also presents the analysis of insights in the process of  students when connecting their knowledge of English with activities and materials in Telematics and Circuits subject class. Key words: perceptions, Language Learning, Specific Purposes.